Kinetic Release Models of Nitrogen and Iron from Chitosan-Biochar Based Slow Release Fertilizers - Martasiana Karbeka (Biology, Medicine, & Natural Product Chemistry, 2026)
The use of slow-release fertilizers (SRFs) is increasingly recognized as a sustainable method to enhance nutrient-use efficiency. This study utilized nitrogen from urea and Fe from iron sand, both encapsulated in chitosan–biochar matrices through NaOH-induced solidification to form bead-type SRFs. Four formulations with different biochar–urea ratios were prepared: A (CB2U2Fe), B (CB3U2Fe), C (CB3U3Fe), and D (CB2U3Fe). Bead morphology was examined using scanning electron microscopy (SEM), while nitrogen and Fe release behavior was evaluated after 1, 3, 5, and 7 days under soil percolation. Release patterns were modeled using pseudo-first-order (PFO), pseudo-second-order (PSO), Weber–Morris, and Elovich kinetics. SEM results showed that chitosan–biochar–urea beads (BCB@N) contained numerous voids and surface cracks, indicating a porous microstructure. In contrast, chitosan–biochar–urea–Fe beads (BCB@UFe) displayed a denser structure with fewer pores, supporting more controlled water entry and nutrient diffusion. Release experiments identified sample C as the most stable formulation for both nitrogen and Fe. Nitrogen-release kinetics fitted the PFO (R² = 0.920) and PSO (R² = 0.954) models, indicating diffusion-driven release with weak surface interactions. Fe-release kinetics for sample C aligned best with the PFO and Weber–Morris models, suggesting dominance of intra-particle diffusion and physisorption processes.